Human exposure pathways to organophosphate flame retardants: Associations between human biomonitoring and external exposure - Fuchao Xu; Igor Eulaers; Andreia Alves; Eleni Papadopoulou; Juan Antonio Padilla-Sanchez; Foon Yin Lai; Line Småstuen Haug; Stefan Voorspoels; Hugo Neels; Adrian Covaci (Environment International, 2019)
Organophosphate flame retardants (PFRs) have largely replaced the market of polybrominated diphenyl ethers (PBDEs). Concerns about PFR contamination and its impact on human health have consequently increased. A comprehensive investigation on the human exposure pathways to PFRs is to be endeavoured. This study investigated the occurrence of PFR metabolites in human urine, serum and hair, correlating them with external exposure data that was presented in our previous studies. Participants from Oslo (n = 61) provided a set of samples, including dust, air, handwipes, food, urine, serum and hair. Associations between PFR metabolites analyzed in the biological samples and the PFRs in environmental samples were explored. Different sampling strategies for dosimeters (e.g. floor/surface dust, personal/stationary air) were also compared to understand which is better for predicting human exposure to PFRs. Seven out of the eleven target PFR metabolites, including diphenyl phosphate (DPHP) and bis(1-chloro-2-propyl)-1-hydroxy-2-propyl phosphate (BCIPHIPP), were frequently detected (DF > 30%) in urine. DPHP was the most frequently detected metabolite in both serum and hair. Several PFR metabolites had higher levels in morning urine than in afternoon urine. Floor dust appeared to be a better proxy for estimating PFR internal exposure than surface dust, air, and handwipes. Some PFRs in handwipes and air were also correlated with their metabolites in urine and hair. Age, beverage consumption and food consumption were negatively associated with DPHP levels in urine. Discrepancies observed between the external and internal exposure for some PFRs call for further investigation on PFR bioaccessibility and clearance. Keywords: PFR metabolites, Exposure pathways, Dust, Air, Handwipe, Urine